Effect of Gum Chewing on Intestinal Functions after Gynecological Operations: A Randomized Controlled Study - Şenol, Taylan; Polat, Mesut; Özkaya, Enis; Ünver, Gökhan; Karateke, Ateş (Gynecology Obstetrics & Reproductive Medicine, 2016)
OBJECTIVE: We aimed to assess the efficacy of gum chewing on intestinal functions after gynecological operations. STUDY DESIGN: A total of 86 women who underwent gynecological operation with different indications were randomly assigned to 2 groups: Group 1 was assigned to gum chewing after operation (n=52), while Group 2 was directed to routine postoperative care (n=52). Time of first bowel sound and defecation after surgery were recorded to assess the effect of gum chewing. Operation time, blood loss, type of incision, pre and postoperative serum hemoglobin levels were all evaluated. RESULTS: There was no difference between groups in terms of age, duration of operation, intraoperative blood loss, pre and postoperative serum hemoglobin levels, duration to first bowel sound, flatulence and defecation (p>0.05). Age (r=0.234, p=0.032), type of incision (r=0.228, p=0.037) were significantly correlated with the time to first bowel sound. Type of incision (r=0.295, p=0.006), duration of operation (r=0.277, p=0.01) and intraoperative blood loss (r=0.298, p=0.006) were significantly correlated with the time to first flatulence. In multivariate regression analyses, none of the variables were found to be significant parameter for time to first bowel sound (p>0.05). CONCLUSION: Gum chewing does not affect some of the gastrointestinal functions after gynecological operations and there is no single parameter for time to first bowel sound, first flatulence and first defecation, individual surgical and medical condition differences should be kept in mind while evaluating intestinal functions.